The evaluation of apical plug formation during endodontic treatment of immature teeth: a case report - Wangidjaja, Bryan; Widyastuti, Wiena; Istanto, Elline; Zulkifly, Dinie Qyrratuaini (Jurnal Kedokteran Gigi Universitas Padjadjaran, 2026)
Introduction: Trauma can cause significant changes in pulpal blood microcirculation, leading to pulp necrosis, arrested root formation, and the development of an open apex. One of the materials recommended for creating an apical plug is mineral trioxide aggregate (MTA). Apical plug formation using biomaterials such as MTA is a common technique for inducing apical closure and facilitating healing. The aim of this case report is to describe the use of the apical plug technique in immature teeth after trauma and to evaluate its effectiveness in achieving apical closure and healing. Case report: A 26-year-old woman visited the Department of Conservative Dentistry due to pain in her upper right anterior tooth. She had dental trauma. Tooth 11 presented with a Class IV composite restoration, and periapical radiographic examination revealed an open apex. A diagnosis of pulp necrosis with symptomatic apical periodontitis and an open apex was established. The apical size of the teeth was determined to be #80. Biomechanical preparation involved circumferential filling technique up to size #100 K-file. MTA with a 4 mm thickness was applied at the open apex, followed by continued obturation. The final restoration was completed using a direct composite restoration. Trauma can result in pulp necrosis, leading to incomplete root development in the immature teeth, which is characterized by thin apex wall and open apex. MTA offers advantages such as antibacterial properties, high marginal adaptation, and a pH of 12.5. In this case, a 6-month follow-up demonstrated healing progression in the periapical region. Conclusion: MTA is an excellent material for use in cases of immature teeth. The success of apical plug formation in this case can be evaluated by the resolution of patient complaints and the healing progress of the periapical region.Evaluasi pembentukan apikal plug selama perawatan endodontik pada gigi imatur: Laporan kasusPendahuluan: Trauma dapat menyebabkan perubahan signifikan pada mikrosirkulasi darah pulpa, menyebabkan kematian pulpa, terhentinya pembentukan akar, dan apeks terbuka. Salah satu material yang direkomendasikan untuk membuat apikal plug adalah mineral trioxide aggregate (MTA). Pembentukan apical plug menggunakan biomaterial seperti MTA merupakan teknik umum untuk menginduksi penutupan apikal dan memfasilitasi penyembuhan. Tujuan laporan kasus ini untuk mendeskripsikan penggunaan teknik apical plug pada gigi imatur paska trauma dengan mengevaluasi efektivitasnya selama penyembuhan. Laporan kasus: Seorang perempuan berusia 26 tahun mengunjungi departemen konservasi karena rasa sakit pada gigi depan atas kanan. Pasien tersebut mengalami trauma dental. Pemeriksaan gigi 11 terdapat restorasi komposit kelas IV, dan melalui pemeriksaan radiograf terlihat adanya apeks terbuka. Ukuran apikal gigi adalah #80. Preparasi biomekanis dilakukan dengan teknik circumferential filing sampai dengan K-file #100. MTA dengan ketebalan 4 mm diaplikasikan pada apeks yang terbuka dilanjutkan dengan obturasi. Restorasi akhir dilakukan dengan komposit direk. Trauma menyebabkan kematian pulpa, sehingga perkembangan akar menjadi tidak sempurna pada gigi yang imatur. Akar yang tidak sempurna terlihat memiliki dinding yang tipis dan apeks terbuka. MTA memiliki kelebihan di antara lain sifat antibakteri, adaptasi marginal yang baik, dan pH 12.5. Pasca perawatan 6 bulan pada kasus ini ditemukan adanya penyembuhan pada bagian apikal dari radiograf. Simpulan: MTA adalah material yang sangat baik yang dapat digunakan pada gigi yang imatur. Keberhasilan pembentukan apical plug pada kasus ini dapat dievaluasi dengan hilangnya keluhan pasien dan adanya proses penyembuhan pada regio periapikal.